(untitled) (Research, Society and Development, 2021)
Symptoms of depression, anxiety and stress have a significant prevalence in Brazilian medical students. This article aimed to identify the prevalences, the assessment instruments used and the associated factors most cited in the national scientific literature. An integrative literature review carried out in the Scielo database and in the Biblioteca Virtual em Saúde (BVS) was used as a method. This review found a wide variation in the prevalence of symptoms of depression, anxiety and stress in Brazilian medical students. Depression was the most evaluated disorder and the symptoms of stress had higher prevalence rates. The associated factors found in this review can be classified in relation to the students’ personal characteristics; family and financial aspects; the student’s perception of the course and his academic performance; factors that interfere with health and quality of life; and psychological aspects such as the presence of stress and a history of psychological or psychiatric treatment.